Study of Simarouba versicolor (Simaroubaceae) associated with the inhibition of the enzyme acetylcholinesterase (Research, Society and Development, 2023)
A particular problem in agriculture is the presence of pests that cause various damages to crops, causing serious economic problems. Currently, a large number of insecticides have been used to control pests. The indiscriminate use of these insecticides results in the abusive use of pesticides and consequent ecological imbalances. New tools such as the isolation of botanical chemicals are playing an increasing role in pest management. Phytochemical properties have different modes of action on insects and other pests including repellency, deterrence, inhibition of motility and respiration, and effect on biochemical cycles such as the enzyme acetylcholinesterase (AChE). The species Simarouba versicolor presents in its constitution substances from the class of flavonoids, triterpenes and quassinoids that can prevent oxidative damage, and this may be associated with the insecticidal properties of this species. The present work sought to evaluate the effects of extracts and fractions of S. versicolor on the inhibition of AChE, contributing to the development of an environmentally correct agricultural defensive associated with the control of agricultural pests. Leaves and branches of S.versicolor were dried and pulverized, and the crude extracts were extracted with solvents in increasing order of polarity (ethyl acetate, methanol and water). The evaluation of the effect of extracts of S. versicolor in natura on the enzyme acetylcholinesterase was determined in microplates by the electrophoretic method at concentrations 1 mg/mL, 0.5 mg/mL, 0.25 mg/mL , 0.125 mg/ml, 0.062 mg/ml, 0.031 mg/ml, 0.015 mg/ml. All extracts presented for the concentration of 0.5mg mL, inhibition greater than 50% characterizing them as potent AChE inhibitors. The species S. versicolor proved to be an inhibitor of AChE.